2020
DOI: 10.1177/0954406220936322
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear superharmonic resonance analysis of a nonlocal beam on a fractional visco-Pasternak foundation

Abstract: This paper investigates the dynamic behavior of a geometrically nonlinear nanobeam resting on the fractional visco-Pasternak foundation and subjected to dynamic axial and transverse loads. The fractional-order governing equation of the system is derived and then discretized by using the single-mode Galerkin discretization. Corresponding forced Mathieu-Duffing equation is solved by using the perturbation multiple time scales method for the weak nonlinearity and by the semi-numerical incremental harmoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…( 58) has to be solved to obtain the data for the next stage. By applying the procedure established at [66,46] elements of the matrix M α 2 , and vectors R α 2 and V α 2 can be expressed as…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 58) has to be solved to obtain the data for the next stage. By applying the procedure established at [66,46] elements of the matrix M α 2 , and vectors R α 2 and V α 2 can be expressed as…”
Section: Discussionmentioning
confidence: 99%
“…( 42)) is introduced in nondimenzionalization process with the purpose to reduce nonlinear parameter θ in Eq. (46). Extreme high values of θ comparing to linear stiffness parameter ω 2 0 would later induce problems with solving fractional-order differential equation of motion (Eq.…”
Section: Beam Model and Equation Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohajed et al 1 with nonlinear dynamic analysis showed the existence of a particular type of modal interactions with a self-adeptness of an attachment to narrow or broadband targeted energy transfers in low or high frequencies. Super-harmonic resonance of a nanobeam with geometric nonlinearities rested on a fractional visco-Paternak foundation in 7 with multiple scale analysis is shown.…”
mentioning
confidence: 99%